Pengaruh Online Learning Self-Efficacy dan Self- Esteem terhadap Prestasi Akademik Mahasiswa STIE YAPAN Surabaya - Mochammad Zuddah Nurmawan; Achmad Sholihin (Sekolah Tinggi Ilmu Ekonomi Yapan, 2022)
Online learning is an alternative for the world of education during a pandemic. Changes in the learning process require a set of behaviors to support learning achievement so that learning achievement does not decline. Online learning self- efficacy and self-esteem can help students improve learning success during the pandemic. This study examines the effect of online learning self-efficacy and self-esteem on academic achievement of STIE YAPAN Surabaya students using quantitative methods. The data of this study consisted of 87 respondents who were active students of the undergraduate program. The results of multiple linear regression analysis show that online learning self-efficacy and self-esteem have a positive and significant effect on academic achievement of STIE YAPAN Surabaya students, either partially or simultaneously. The respondents' online learning self-efficacy and self- esteem contributed 37.2% to the academic achievement of STIE YAPAN Surabaya students.